Studying the organization of the Golgi by super-resolution microscopy - Tie, Hieng Chiong (2023)
The Golgi complex is essential for protein transport and posttranslational modification in mammalian cells. It is critical to know the cisternal distribution of Golgi proteins to understand Golgi functions. The cis-to-trans or axial localization of a Golgi protein can be obtained using our previously developed method, Golgi protein localization by imaging centers of mass (GLIM), in nocodazole-induced Golgi ministacks (hereafter referred to as ministacks). However, there is no effective light microscopic method to reveal the lateral localization of a Golgi protein, which is the distribution within the Golgi cisternae. The challenge is partially caused by the random orientations and the tight congregation of Golgi stacks at the perinuclear region. Here, we summarize our method to identify en face and side views of ministacks. It takes advantage of the characteristic ring and double-punctum staining patterns exhibited by cisternal rim-localized proteins. After averaging multiple en face views, the resulting image reveals the intrinsic organization of cisternae in a non-biased manner.